2008
DOI: 10.1007/s10238-008-0174-y
|View full text |Cite
|
Sign up to set email alerts
|

Megalin and cubilin in the human gallbladder epithelium

Abstract: Although the role of cholesterol absorption by the gallbladder epithelium in gallstone formation is well established, the exact process is poorly understood. Potential candidates for regulation of transepithelial cholesterol transport are suggested to be two large membrane multiple ligand receptors, megalin and cubilin. We studied the expression of these two proteins in both acalculous and calculous human gallbladder epithelia. Adult human gallbladder tissues were received from 21 patients (9 men, 12 women) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
13
0
5
Order By: Relevance
“…Interestingly, the anatomic malformations observed with PA in humans are consistent with the defects in the outflow tract in the zebrafish model [31], [32]. Cubilin, encoded by CUBN , is a receptor expressed in the apical pole of absorptive epithelia [33], and it plays an important role in the absorption of vitamin B 12 [34]. The interactions between folate, vitamin B 12 , and homocysteine are summarized in Figure 1C.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, the anatomic malformations observed with PA in humans are consistent with the defects in the outflow tract in the zebrafish model [31], [32]. Cubilin, encoded by CUBN , is a receptor expressed in the apical pole of absorptive epithelia [33], and it plays an important role in the absorption of vitamin B 12 [34]. The interactions between folate, vitamin B 12 , and homocysteine are summarized in Figure 1C.…”
Section: Discussionsupporting
confidence: 58%
“…Gallstone disease is a multifactorial condition of the gallbladder, which involves genetic, sex, age and environmental variables (Lammert and Miquel, 2008). A study of a small number of gallstone patients in the Greek population found that both megalin and cubilin were downregulated in gallstone patients at the mRNA and protein levels (Tsaroucha et al, 2008). On the other hand, we have found that gallstone-susceptible mice fed a cholesterolrich lithogenic diet showed a reduction in megalin mRNA expression (Fig.…”
Section: Megalin In Gallstone Diseasementioning
confidence: 81%
“…Megalin is also present in the kidney, lung and thyroid (Willnow et al, 1996;Lundgren et al, 1997;Marino et al, 1999), epydidimis (Hermo et al, 1999), mammary gland (Lundgren et al, 1997;Rowling et al, 2006) and gallbladder (Erranz et al, 2004;Tsaroucha et al, 2008).…”
Section: Role Of Megalin In the Kidney And Other Organsmentioning
confidence: 99%
“…They are primarily expressed in polarized epithelial cells with a few exceptions. For instance, cubilin has been identified in several types of cells from different species, including epithelial cells from proximal tubules (rat [153], dog [59], mice and humans [150]), yolk sac (rat [153] and human [165]), small intestine (canine [166], rabbit [167], dog [168] and rat [163]), glomerular podocytes (rat and human [169]), inner ear (rat [170]), lung (human [171]), gallbladder (human [172]), mammary (murine and human [173]), uterus and oviduct (human [174]) as well as placental syncytiotrophoblasts and cytotrophoblasts (human [165]). In most cases, cubilin is co-expressed with megalin, where both are located at the apical membranes [167,[175][176][177].…”
Section: Cubilin and Megalin -Multibinding Endocytic Proteins With Afmentioning
confidence: 99%